Assessing Factors Affecting M&As versus Greenfield FDI in Emerging Countries - Hyung-Suk Byun; Hyun-Hoon Lee; Cyn-Young Park (Asian Development Bank (ADB), 2012)
A host of external (global and regional) and internal (country-specific) factors affect Multinational Enterprises' Foreign Direct Investment (FDI) decisions. Differentiating the two entry modes of FDI (mergers and acquisitions [M&A] and Greenfield investment), this paper aims to empirically assess whether or not being a part of global emerging market economies or any specific emerging regions affects investors' decisions of FDI flows to an emerging country in addition to various country-specific factors. For this purpose, this paper employs a system generalized method of moments estimator for the panel data consisting of 40 emerging countries for the period 1990–2009. The results suggest that there exist a strong and significant global and regional influence in both types of FDI flows to an emerging country. M&A appears to be more sensitive to external factors, both global and regional effects are about twice stronger for M&A than for Greenfield FDI. The results also suggest that country- specific factors matter a lot for FDI flows both in the form of M&A and Greenfield FDI, pointing to the importance of government roles in helping stabilize FDI flows to emerging countries. This paper also offers empirical evidence which is consistent with the phenomenon of a fire-sale FDI during the period of financial crisis. Additional evidence using extensive and intensive margins of M&A sales suggest that the fire-sale does not necessarily imply an increase in the number of deals, but it may reflect the sales of big firms during the crisis.
hdl:11540/1267
Keywords: 330; Übernahme; Multinationales Unternehmen; Greenfield-Investition; Schwellenländer; Welt